2014
DOI: 10.1039/c4cy00526k
|View full text |Cite
|
Sign up to set email alerts
|

Searching for cheaper catalysts with high activity and stability in Ce–M–O systems (M = Fe, Co, Ni)

Abstract: A cheaper catalyst with enhanced catalytic activity and stability was investigated among Ce–M–O (M = Fe, Co, Ni) systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 81 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…All peaks of the samples consisted primarily of CeO 2 phase (JCPDS 34-0394) without any detectable diffraction peak of iron oxide. Similar phenomenon was found in other studies when Fe level was varied in the range from 5% to 15% [24]. Reflection peaks observed at 2h = 28.7°, 33.2°, 47.6°and 56.5°were well assigned to the (1 1 1), (2 0 0), (2 2 0) and (3 1 1) planes of face-centered cubic-phase CeO 2 .…”
Section: Sem Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…All peaks of the samples consisted primarily of CeO 2 phase (JCPDS 34-0394) without any detectable diffraction peak of iron oxide. Similar phenomenon was found in other studies when Fe level was varied in the range from 5% to 15% [24]. Reflection peaks observed at 2h = 28.7°, 33.2°, 47.6°and 56.5°were well assigned to the (1 1 1), (2 0 0), (2 2 0) and (3 1 1) planes of face-centered cubic-phase CeO 2 .…”
Section: Sem Analysissupporting
confidence: 82%
“…The diclofenac degradation efficiency decreased with mole ratio of Fe and Ce increasing from 1:9 to 5:5, indicating that excessive active ions would be harmful to catalytic activity of FeCeO x due to agglomeration on the surface. Furthermore, Zuo et al studied the preparation of Ce-M-O solid solutions (M = transition metal) with high activity and stability, and found that Ce 0.9 M 0.1 O 2 (M = Fe, Co, Ni) could form solid solution structure with high solubility limit [24]. When tested as the catalysts for CO oxidation, the solid solution of Ce 0.9 M 0.1 O 2 maintained excellent catalytic performance as that in our study.…”
Section: Effect Of Mole Ratio Of Fe and Cementioning
confidence: 98%
“…22‐700 [4d] as a typical LDH structure) [3,4a–d] were largely confirmed in both samples, and iron oxide hydroxide (α‐FeOOH, JCPDS No. 29‐0713 [4e] ) derived from trivalent iron species was also formed as a by‐product (Figure 2(A) and Table S1). The diffraction peaks ascribed to the (003) and (006) planes of Fe 2+ Al 3+ ‐LDH‐SO 4 2− were shifted significantly toward lower angles compared with the peaks from Fe 2+ Al 3+ ‐LDH‐Cl − , suggesting that the interlayer distance of Fe 2+ Al 3+ ‐LDH‐SO 4 2− increased more in this material than in Fe 2+ Al 3+ ‐LDH‐Cl − by the introduction of SO 4 2− , which is a larger anion than Cl − [4a] .…”
Section: Resultsmentioning
confidence: 99%
“…Ceria (CeO 2 ) has outstanding thermal stability and facile oxygen kinetics between its surface and the atmosphere, so the compound has been applied as a catalyst in many industrial applications. Especially, it has been used as an active component in three-way catalytic converters of internal combustion engines to perform the redox reactions that convert pollutants of exhaust gases to less harmful ones. …”
Section: Introductionmentioning
confidence: 99%